Phenoxycarboxlic acid Toxicity Test on Vannamei Shrimp (Litopenaeus vannamei) Mortality - Lisna Lisna; Mainisa; Erlangga Erlangga; Saiful Adhar; Munawwar Khalil (Fakultas Pertanian Universitas Samudra, 2023)
This study aims to examine the toxicity of phenoxy acid herbicides on vannamei shrimp mortality, by conducting preliminary tests, persistence tests, mortality tests, and water quality. The research design used the regression method and probit analysis with 6 treatments and 3 replications, namely A herbicide concentration of 0 ml/L, B herbicide concentration DMA-6, 0.025 ml/L water, C herbicide concentration DMA-6, 0.005 ml/L water, D DMA-6 herbicide concentration, 0.075 ml/L water, E DMA-6 herbicide concentration, 0.1 ml/L water and F DMA-6 herbicide concentration, 0.125 ml/L water. Pesticides do not affect temperature changes, dissolved oxygen (DO), Salinity, and pH. Clinical symptoms due to Pesticide exposure to vanamei shrimp are irregular movements, shells peeling off, and swimming close to aeration until they die. The LC50 value in the herbicide toxicity test was 0.124 mg/l at 24 hours, 0.099 mg/l at 48 hours, 0.073 mg/l at 72 hours, and 0.026 mg/l at 96 hours.